Computer Literacy Study: The Digital Divide Among New Students: A Case Study of the Undergraduate Program in Computer Science An Nasher University Cirebon - Yusep Saepulloh (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Digital transformation has shifted the educational paradigm but raised a serious challenge: the digital divide. At An Nasher University Cirebon, the "digital native" label among new students does not necessarily align with academic technological proficiency, leading to a "second-level digital divide" that hinders equitable learning quality. This study aims to explore the level of computer and digital literacy among new students of the Computer Science Undergraduate Program and identify socio-economic and geographical factors causing the digital gap. This study employed a descriptive quantitative approach involving 120 new students from the 2024 cohort selected via purposive sampling. Data were collected through online questionnaires using a Likert Scale to measure four dimensions: technical, communication, critical, and ethical. The data were analyzed using descriptive statistical techniques and Average Achievement Level (TCR) calculations. The results indicate that the overall digital literacy level is in the "Fair" category (TCR 75.8%). Although the basic functional aspect is "Good" (81%), significant weaknesses were found in the ethical (70%) and critical thinking (75.6%) dimensions. The main factors of the digital divide are the inequality of laptop ownership (29.2% of students do not own a laptop) and infrastructure disparities between the Cirebon City and Regency areas.